Sex differences in behavioral measures of anxiety in a recessive gene knockout (Pink1–/–) rat model of Parkinson’s disease - Feehan, S. M.; Kritzer, M. F. (Frontiers in Behavioral Neuroscience, 2025)
IntroductionParkinson’s disease (PD) is characterized by non-motor impairments including symptoms anxiety. These disturbances manifest in up to 40% of patients, most often early in the course of disease. While disruptive to all patients’ lives, signs of anxiety are also more prevalent and/or more severe in female PD patients. Unfortunately, anxiolytic drugs are rarely used to manage these signs, as these medications can increase PD patients’ risks for worsening of cognitive deficits and falls. The treatments commonly used in PD to improve patients’ motor function or lessen signs of depression are often without positive effect on measures of anxiety. Thus, clinical needs for successful treatment of anxiety symptoms in PD are frequently unmet.MethodsThe work presented here used longitudinal Elevated Plus Maze (EPM) testing in male and female wild type rats and in male and female rats with knockout of the PTEN-induced putative kinase 1 gene (Pink1–/–) to determine whether these are suitable models for translational studies examining the neural substrates that underpin the sex-specific expression of anxiety symptoms in PD.ResultsBehavioral testing in male and female wild type and Pink1–/– rats showed that Pink1–/– rats of both biological sex initially displayed hyperlocomotion and broad, possibly impulsive exploration of all portions of the elevated plus maze, including its open, unprotected spaces. While these behaviors persisted in Pink1–/– males, by 7 months of age, EPM performance in female Pink1–/– rats changed dramatically and included convergent behavioral measures indicative of significantly heightened anxiety, e.g., reduced open arm entries, slower speeds of ambulation in open arms, avoidance of distal ends of open arms. These and other signs of an anxiety remained through final testing of the female Pink1–/– cohort at 12 months of age.DiscussionUnlike a surprising number of other rodent models of PD that fail to emulate clinically observed anxiety and/or male/female differences in these signs, the data presented here identify Pink1–/– rats as strongly suited to lead translational efforts to better understand the neurobiological and neuroendocrine bases for anxiety symptoms in PD, their sex differences and their sex-specific sensitivities to therapeutic interventions.